2009
DOI: 10.1007/s00268-009-0249-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Gallbladder Cancer Diagnosed Following Laparoscopic Cholecystectomy

Abstract: Male patients exhibited aggressive tumor characteristics. Laparoscopic cholecystectomy is an adequate treatment for pT1 tumors. For pT2 and pT3 patients, additional radical surgery might be needed to achieve a tumor-free surgical margin, along with lymph node dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 56 publications
2
42
2
1
Order By: Relevance
“…The incidence of gallbladder cancer detected after LC has been reported to be 0.54%-2.1% (27)(28)(29). Gallbladder carcinoma was detected in 7 patients (2.4%) in our study.…”
Section: Discussionsupporting
confidence: 43%
“…The incidence of gallbladder cancer detected after LC has been reported to be 0.54%-2.1% (27)(28)(29). Gallbladder carcinoma was detected in 7 patients (2.4%) in our study.…”
Section: Discussionsupporting
confidence: 43%
“…The incidence of gallbladder cancer detected after LC has been reported as 0.54%-2.1% (27)(28)(29). Gallbladder carcinoma was detected in seven patients (2.4%) in our study.…”
Section: Mostmentioning
confidence: 73%
“…(Grade 1, evidence level C) Statement: It is reported that the frequency of the incidental gallbladder carcinoma that is found serendipitously by postoperative pathological examination is reported to be 0.3-1.0% in gallbladder resected for cholacystolithiasis [176][177][178][179]. In patients in whom the histological analysis using whole gallbladder serial sections reveals the depth of cancer invasion limited to the mucosa or muscularis propria, an additional resection is not necessary if the cystic duct stump is negative.…”
Section: Cq16: What Are Considered As Unresectable Factors In Biliarymentioning
confidence: 99%